Solving Nonlinear Differential Algebraic Equations by an Implicit Lie-Group Method - Chein-Shan Liu (Journal of Applied Mathematics)
We derive an implicit Lie-group algorithm together with the Newton iterative scheme to solve nonlinear differential algebraic equations. Four numerical examples are given to evaluate the efficiency and accuracy of the new method when comparing the computational results with the closed-form solutions.